Our clinical experience of Takotsubo cardiomyopathy and the first case series from Turkey - Zekeriya Küçükdurmaz; Hekim Karapınar; Mehmet Burhan Oflaz; İbrahim Gül; Gülay Aydın; Hakan Güneş; Ahmet Yılmaz (KARE Publishing, 2013)
Objectives: There is no data about the incidence, progress and prognosis of Takotsubo Cardiomyopathy (TC) from Turkey. This study aimed to search for the progress and shortterm prognosis of TC patients and to increase the familiarity and awareness for TC in Turkey. Study design: We included 6 patients who were referred to our center with ST elevation myocardial infarction and diagnosed as TC according to the Mayo Clinic diagnostic criteria. Results: Our patients' median age was 46 years (range 17 to 64 years) and 3 of them were males. Triggering factors included emotional stress (3 patients) and physical stress (3 patients). Median troponin I level was 1.65 ng/ml (0.48-2.20), excluding the patients who underwent cardiopulmonary resuscitation. ST elevation in precordial leads was observed on the ECG of 4 patients and in inferior leads on ECG of 2 patients. Five patients' coronary arteries were normal and were diagnosed as typical, but 1 patient had non-critical stenosis on the coronary arteries and was diagnosed with reverse TC. Four patients were discharged without any complications but 2 presented with sudden cardiac death. Conclusion: This study presented the first data about TC in Turkey while attempting to increase awareness about the disease. Emergent ventricle evaluation by ventriculography or echocardiography is recommended for acute coronary syndrome patients with non-critical stenosis for the differential diagnosis.